2007
DOI: 10.1007/s00192-007-0494-6
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic variations of the pelvic floor nerves adjacent to the sacrospinous ligament: a female cadaver study

Abstract: Our objective was to document variations in the topography of pelvic floor nerves (PFN) and describe a nerve-free zone adjacent to the sacrospinous ligament (SSL). Pelvic floor dissections were performed on 15 female cadavers. The course of the PFN was described in relation to the ischial spine (IS) and the SSL. The pudendal nerve (PN) passed medial to the IS and posterior to the SSL at a mean distance of 0.6 cm (SD = +/-0.4) in 80% of cadavers. In 40% of cadavers, an inferior rectal nerve (IRN) variant pierce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
1
22
0
4
Order By: Relevance
“…Separate entry of the IRN into the gluteal region is not an uncommon occurrence and varies between populations and studies performed. Mahakkanukrauh et al [15] reported a 20.5% occurrence in an Asian cadaver study, Shafik et al [16] noted a 20% occurrence in an Egyptian cadaver study, Lazarou et al [22] reported a 40% occurrence in an American cadaver study, and Achtari et al [30] noted a 10% occurrence in an Australian cadaver study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate entry of the IRN into the gluteal region is not an uncommon occurrence and varies between populations and studies performed. Mahakkanukrauh et al [15] reported a 20.5% occurrence in an Asian cadaver study, Shafik et al [16] noted a 20% occurrence in an Egyptian cadaver study, Lazarou et al [22] reported a 40% occurrence in an American cadaver study, and Achtari et al [30] noted a 10% occurrence in an Australian cadaver study.…”
Section: Discussionmentioning
confidence: 99%
“…The IRN may also arise from the pudendal trunk before it enters the pudendal canal [18]. Various studies have described an incidence of 12.5-40% of individual gluteal entry of the IRN, where it did not branch from the PN in the gluteal region [15,16,21,22]. Towards the distal end of Alcock's canal, the PN bifurcates, giving rise to two terminal branches, the perineal nerve and the dorsal nerve of the penis or clitoris [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…The PN originates from the section of the upper cord of the ventral ramus of sacral roots 2 through 4. The lower cord is formed by the union of the rami of sacral nerves 3 through 4 [2][3][4][5][6].…”
Section: Pudendal Nerve Neuroanatomymentioning
confidence: 99%
“…Es wurden bei 0,5 % der Fälle Gefäßver-letzungen und bei 0,4 % Rektumläsionen festgestellt; bei 5,2 % mussten Bluttransfusionen durchgeführt werden. Ipsilaterale gluteale Schmerzen ("Buttock Pain"), die auf eine Kompromittierung des N. rectalis inferior zurückgeführt werden können und z. T. selbstlimitierend verlaufen, werden in 3 -15 % der Fälle beschrieben [13][14][15]. Gravierende …”
Section: Vaginale Suspensionstechniken Am Ligamentum Sacrospinaleunclassified